SDG17 : partnerships for the goals : strengthening implementation through global cooperation - Thiel, Monica (Bingley, U.K. : Emerald Publishing Limited, 2019)
Partnerships are often implemented in various ways, often without considering the impact, process or systemic performance and governance level of the partnership itself. The current bank of knowledge also offers little about complex partnership performance logics and multi-level governance across sectors. Partnership concerns can often be predominately focused on opportunistic business goals and benefits rather than the systemic partnering process itself. But partnerships do not operate in a vacuum.This book leads with the idea that partnerships can drive change. It argues that current partnership practices may impede sustainable business benefits and increase risk through a disregard for excellence, the ethics of care, and consideration for how partnership performance can directly affect corporate value and public value. The book utilizes comprehensive critical analyses and collaborative strategies to help readers learn how to formulate, integrate, implement, and monitor partnership performance. The book concludes that business and global development concerns are not independent of partnership concerns.Concise Guides to the United Nations Sustainable Development Goals comprises 17 short books, each examining one of the UN Sustainable Development Goals. The series provides an integrated assessment of the SDGs from economic, legal, social, environmental and cultural perspectives.
Prelims -- Introduction -- 1. Defining a partnership -- 2. Collaborative performance -- 3. Collective governance -- 4. Examining partnership success and failure -- 5. Collective intelligence -- 6. Partnership intervention strategies -- 7. Integrated partnership performance among government, business and civil society -- 8. Connecting partnerships with responsible investments -- References -- Index.
Includes bibliographical references and index.
Keywords: Partnership; International cooperation; Political Science -- Public Policy -- Environmental Policy; Environmental management